Polymorphism of Glutathione-S -Transferase P1 gene in Breast Cancer patients in Baghdad /Iraq - Muftin, Najlaa Qassim (Iraqi Journal of Cancer and Medical Genetics, 2015)
Glutathion S-transferase enzymes are detoxifying enzymes – phase II enzymes, which play an important role in protecting cells from damage caused by endogenous and exogenous compounds and subsequently, are crucial in protecting the DNA. The aim of this study is to evaluate polymorphism of Glutathion S-transferase P1 (GSTP1) in Iraqi women breast cancer. Blood samples were collected from 65 Iraqi women diagnosed as breast cancer patients who attended to Oncology Teaching Hospital and Al-Yarmouk Teaching Hospital. In addition to 59 healthy women as control group. Genomic DNA was extracted then genotyping was performed by restriction fragment length polymorphism- polymerase chain reaction (RFLPPCR) for GSTP1 gene. The frequencies of GSTP1 polymorphism (Ile105Val) in the breast cancer group were: 41.54% for wild type (Ile/Ile), 49.23% for heterozygote (Ile/Val) and 9.23% for homozygote mutant (Val/Val), while in control group was 57.63 for wild (Ile/Ile), 42.37(Ile/Val) heterozygote and 0.00 %(Val/Val) homozygote. The results show there were statistically significant differences in the distribution of (Val/Val) genotype and Val allele between patients and controls groups (p<0.05), (OR= 16.3091; 95% CI= 0.8798 to 302.3326) and (OR= 1.9380; 95% CI= 1.0274 to 3.6556) respectively . This study showed that GSTP1 (Val/ Val) genotype may be associated with an increased risk for breast cancer among Iraqi women.